Moderation of Firm Size and Intellectual Capital on the Effect of Profitability on Firm Value (E-Jurnal Akuntansi, 2026)
The research aims to examine the effect of profitability on firm value with the moderating variables of firm size and intellectual capital. The population of this research is 47 mining companies listed on the Indonesia Stock Exchange in 2016–2020. The research sample used purposive sampling so that 29 companies were selected with a period of 5 years of observation, so a sample of 145 observations was obtained. The data analysis technique used Moderated Regression Analysis (MRA). This research finds that profitability, firm size and intellectual capital have a positive and significant effect on firm value. Firm size and intellectual capital can moderate the positive effect of profitability on firm value. This type of moderation includes quasi-moderation in which the two moderating variables that interact with the independent variable (profitability) are also independent variables.
Keywords: Firm Size; Intellectual Capital; ROE; and PBV